(untitled) (Revista de Ciências Agroveterinárias, 2018)
The mechanisms of seeding machines to cut the mulch, mobilize the topsoil and deposit the seeds in the furrows modify soil properties and interfere in crop growth. This study sought to evaluate the effects of furrow openers and scarification on the attributes of a South Brazilian latosol (Bruno – oxisol) and crop yields. The treatments were: double disc furrow opener (DD); shovel type furrow opener (S); shoe type furrow opener (SH); and scarification followed by double disc furrow opener (SC+DD). Samples were collected at 0-10, 10-20 and 20-40 cm and evaluated for soil physical (bulk density, total porosity, macro and microporosity), chemical (pH, Ca, Mg, K and P) and organic carbon content. The normality of data was tested, and the analysis of the variance was performed (F test, p<0.05), and the means was compared by Tukey’s test (p=0.05). Soil attributes were analyzed for each layer separately. After four years it was observed that the bulk density is still affected by scarification, which reduces it. The successive use of DD in the winter for the implantation of the crops caused the homogenization of the soil, although with no differences on the other physical and chemical properties. In general, grain yield and dry mass were higher in the treatment that used scarification and the double disc during the summer, and the shoe type when compared to shovel type.